Kontribusi TGH Lalu Muhamad Nuh dalam Upaya Meningkatkan Kecerdasan Spiritual Santri Pondok Pesantren Qudwatusolihin Pemondah Pandan Wangi - Muhammad Hanafi; Nasrullah Nasrullah; Zaibun Irmawadi (PALAPA, 2025)
Spiritual intelligence is a vital dimension in the development of a holistic personality, reflecting one' S capacity to actualize Divine values in everyday life. In the modern era, it serves as an essential complement to intellectual and emotional intelligence and can be cultivated through religious approaches and closeness to Allah Swt. This study examines the contribution of TGH Lalu Muhamad Nuh in enhancing the spiritual intelligence of students at Pondok Pesantren Qudwatussolihin through his three primary roles: as a role model, motivator, and educator. Employing a qualitative case study approach, data were collected through interviews, documentation, and observation. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that (1) as a role model, TGH Lalu Muhamad Nuh encourages students to embody politeness, tepo seliro, and personal accountability in acknowledging mistakes and seeking forgiveness; (2) as a motivator, he fosters spiritual development by enhancing self-confidence, emotional regulation, positive speech, and student creativity; (3) as an educator, he consistently emphasizes the importance of istiqomah in both religious practice and daily life. The study concludes that the comprehensive role of TGH Lalu Muhamad Nuh significantly contributes to the cultivation of students' Spiritual intelligence, as reflected in their attitudes, behaviors, and religiously grounded mindset. These findings contribute to the reinforcement of spiritually based educational models and offer a reference for character development practices in Islamic boarding school environments.